A Qualitative Study of Beginner Students’ Experiences and Perceptions in Arabic Language Learning at MTs Babul Mujahidin Bayan, Lombok Utara - Yesinta Isnaini; Mustar Mustar; Yogia Prihartini; Dina Chabib Uluum; Maryam Amiri Al- Hamami; Putri Hardiyanti (UIN Mahmud Yunus Batusangkar, Indonesia, 2025)
Arabic language learning plays a vital role for Muslims, serving not only as a means of communication but also as an integral component of religious practice. Despite this, many beginner-level students face difficulties in understanding Arabic lessons, particularly in madrasahs where Arabic has not yet become a primary focus. This study aims to explore beginner students’ perceptions of Arabic language learning at MTs Babul Mujahidin Bayan, Lombok Utara, to provide insights for designing more effective instructional strategies. A descriptive qualitative approach was employed, involving six eighth-grade students as participants. Data were collected through in-depth semi-structured interviews and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that while students demonstrate a relatively high interest in learning Arabic, they struggle with reading Arabic texts and comprehending classroom materials due to limited foundational skills and monotonous teaching methods. Nonetheless, students expressed positive attitudes and a desire for more engaging and interactive learning processes, such as gamified activities and visual media. The study contributes to Arabic language education by highlighting the importance of incorporating student-centered, interactive strategies at the beginner level, offering evidence-based recommendations for improving instructional design in madrasah settings.